2018
DOI: 10.17219/acem/94143
|View full text |Cite
|
Sign up to set email alerts
|

Study of antinociceptive effect of ketamine in acute and neuropathic pain models in rats

Abstract: Background. Glutamate N-methyl-D-aspartate (NMDA) receptors are known for their importance in the perseverance of chronic neuropathic pain. Ketamine, an intravenous anesthetic agent, is a non-competitive blocker of NMDA receptors. Applied in anesthetic doses, ketamine has anti-nociceptive effects in various animal pain models. Objectives. The objective of this study was to investigate the anti-nociceptive effect of ketamine in acute and neuropathic pain models in rats. Material and methods. To study the anti-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…In this study, the DIVAS scores in the group treated with amantadine were significantly lower than those in the control group. This result is consistent with those of previous studies in which other NMDA receptor antagonists reduced postoperative pain from thoracotomy in humans (Moyse et al, 2017) and demonstrated antinociceptive effect in rats (Wolinska et al, 2017;Doncheva et al, 2019) and in dogs undergoing ovariohysterectomy (Slingsby and Waterman-Pearson, 2010;Almeida et al, 2013;Shah et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the DIVAS scores in the group treated with amantadine were significantly lower than those in the control group. This result is consistent with those of previous studies in which other NMDA receptor antagonists reduced postoperative pain from thoracotomy in humans (Moyse et al, 2017) and demonstrated antinociceptive effect in rats (Wolinska et al, 2017;Doncheva et al, 2019) and in dogs undergoing ovariohysterectomy (Slingsby and Waterman-Pearson, 2010;Almeida et al, 2013;Shah et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…The cut-off imposed was 30 s to avoid tissue damage. The reaction time was subsequently assessed 1-6 months after chronic oral treatments (Doncheva et al, 2019). The data were collected by an observer who was blinded to the protocol.…”
Section: Hot Plate Testmentioning
confidence: 99%
“…Further, a meta-analysis showed that KET analgesic effect persists for at least 4 weeks (Niesters et al, 2014), which was in line with the long-lasting impact of KET in our study. Despite the long-lasting effects of IT KET on sensory-motor dysfunction, Doncheva et al (2019) found that 14-day IP injection of KET showed an early and short-lasting analgesic effect in a rat model of sciatic nerve ligation as evaluated by formalin, analgesia-meter and hot plate tests. In the current study, pain and motor performance were assessed from the 7 th day to 28 th day post-injury.…”
Section: Discussionmentioning
confidence: 93%